Reduction of three-phase voltage unbalance subject to special winding connections of two single-phase distribution transformers of a microgrid system using a designed D-STATCOM controller - Li Wang; Wei-Sheng Liu; Chuan-Chieh Yeh; Chien-Hsiang Yu; Xiu-Yu Lu; Bing-Lin Kuan; Prokhorov, Anton V. (2017 IEEE Industry Applications Society Annual Meeting, 2017)
The U-V or V-V winding connections of two single-phase distribution transformers are widely utilized in distribution systems to deliver power to various three-phase and/or single-phase loads. Such special winding connections of distribution transformers can cause three-phase voltage unbalance in distributions systems, which could also lead to unexpected trip of ground relay, extra power losses on distribution-system lines, reduced operating efficiency of induction-motor loads, etc. This paper proposes a distribution static synchronous compensator (D-STASTCOM) to effectively improve the voltage unbalance of a distribution system connected with a microgrid system. The studied microgrid system contains various renewable-energy resources, a diesel-engine generator, and three distribution transformers with U-V and/or V-V winding connections. The simulation results show that the proposed D-STATCOM with the designed controller can effectively reduce voltage unbalance of the distribution system connected with the studied microgrid system when the distribution transformers have U-V and/or V-V winding connections.